Trefoil factors share a lectin activity that defines their role in mucus - Michael A. Järvå (Nature Portfolio, 2020)
Trefoil factors (TFFs) protect the mucosa and have various reported binding activities, but whether they share a common interaction mechanism has remained unclear. Here, the authors provide structural and biochemical evidence that all three human TFFs are divalent lectins that recognise the same disaccharide.